Factors Influencing Social Interactions among Nursing Home Residents (Case Study: Golabchi Nursing Home, Kashan, Iran) - Shabnam Baghban Kashani (Journal of Global Pharma Technology, 2018)
The present study aimed to find effective factors in promoting social interactions among elderly people as a factor influencing participation of the elderly population. The factors promoting social interactions between Golabchi nursing home residents were identified and classified using questionnaires, interviews and field observations. Then, the factors required to suitable design housing for them were identified. Afterwards, the data was analyzed and finally the most important factors promoting social interactions among nursing home residents were presented. Descriptive-analytical survey was used to conduct this research and data were imported into SPSS to be analyzed. The results showed that among the 27 identified factors related to residential satisfaction, learn ability, communicability, ease of access, walk ability, exercisability, and space standardization, had the maximum impact on increasing happiness, hope and safety in elderly people. These factors will ultimately lead to promote interactions among the elderly population.Keywords: Design for elderly, Social interaction, Personal satisfaction, Physical space.